Pengaruh Partisipasi Karyawan Terhadap Kinerja Keselamatan dan Kesehatan Kerja Rumah Sakit (K3RS) Santo Borromeus - Tanti - Winarti; Banowati - Talim (Universitas Kristen Maranatha, 2018)
Occupational safety and health is an effort to provide safety assurance and improve the health of workers by prevention of occupational accidents and diseases, hazards in the workplace, health promotion, treatment and rehabilitation. Hospitals have a variety of potential hazards, therefore Hospital is required to implement safety and health efforts through the implementation of safety and health management work carried out in an integrated and comprehensive. Employee participation is an important factor in improving safety and health performance.This study aims to determine and analyze the extent of the influence of employee participation on the performance of occupational safety and health of Hospital Santo Borromeus. This type of research is a survey study, supported by the spread of questionnaires as a means of data collection. The research method used is a mix method with descriptive analysis technique. Other research data were obtained from interviews, observations, and document studies. This study was restricted to the Laboratory unit and the Central Sterilization Supply Department (CSSD) unit of Santo Borromeus Hospital. The results showed that employee participation has a significant influence on the performance of occupational safety and health of Santo Borromeus Hospital with total influence of 31.2%. And based on the result of correlation analysis, the type of work accident has a significant influence on job position, this is proved by significance value <0,05.Â Keywords:Employee Participation, Occupational Health and Safety Hospital, Occupational Types